2013
DOI: 10.3390/molecules18033339
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Click Chemistry for Single-Chain Nanoparticle Construction

Abstract: Single-chain polymeric nanoparticles are artificial folded soft nano-objects of ultra-small size which have recently gained prominence in nanoscience and nanotechnology due to their exceptional and sometimes unique properties. This review focuses on the current state of the investigations of click chemistry techniques for highly-efficient single-chain nanoparticle construction. Additionally, recent progress achieved for the use of well-defined single-chain nanoparticles in some promising fields, such as nanome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
145
0
5

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(151 citation statements)
references
References 62 publications
1
145
0
5
Order By: Relevance
“…22 To date, copper-mediated azide-alkyne cycloaddition, 8,[34][35][36] thiol-ene addition, 37,63 and amine-isocyanate addition 32 click reactions have been used as cross-linking methods for SCNP fabrication. 22 To date, copper-mediated azide-alkyne cycloaddition, 8,[34][35][36] thiol-ene addition, 37,63 and amine-isocyanate addition 32 click reactions have been used as cross-linking methods for SCNP fabrication.…”
Section: Rhodium Coordination 61mentioning
confidence: 99%
“…22 To date, copper-mediated azide-alkyne cycloaddition, 8,[34][35][36] thiol-ene addition, 37,63 and amine-isocyanate addition 32 click reactions have been used as cross-linking methods for SCNP fabrication. 22 To date, copper-mediated azide-alkyne cycloaddition, 8,[34][35][36] thiol-ene addition, 37,63 and amine-isocyanate addition 32 click reactions have been used as cross-linking methods for SCNP fabrication.…”
Section: Rhodium Coordination 61mentioning
confidence: 99%
“…Supramolecular folding of polymer chains into single chain polymeric nanoparticles (SCPNs) is an attractive alternative to prepare compartmentalized, water-soluble, nanometersized particles with a hydrophobic interior. [29][30][31][32] Notably, the benzene-1,3,5-tricarboxamide (BTA) is an attractive unit to form SCPNs with well-defined, conformationally adaptable, three-dimensional structures as a result of the hydrogenbond-driven, helical self-assembly of the BTA units. 31 Detailed scattering studies revealed that water-soluble copolymers based on oligo(ethylene glycol) methacrylate (oEGMA) and benzene-1,3,5-tricarboxamide methacrylate (BTAMA) fold in water into compact conformations Additional Supporting Information may be found in the online version of this article.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] SCNPs based on self-collapsed individual chains mimic the structure of folded biomacromolecules although in a rough, primitive manner. [7][8][9][10][11][12][13][14] Recently, we have demonstrated a very efficient strategy for the construction of transient binding disordered protein-mimic nano-objects based on SCNPs. 15 Small angle neutron scattering (SANS) and molecular dynamics (MD) simulation results undoubtedly showed that the form factor of these SCNPs in solution resembles that of intrinsically disordered proteins (IDPs).…”
mentioning
confidence: 99%